A new general formula for the Cauchy index on an interval with subresultants. (March 2022) - Perrucci, Daniel; Roy, Marie-Françoise
Abstract: We present a new formula for the Cauchy index of a rational function on an interval using subresultant polynomials. There is no condition on the endpoints of the interval and the formula also involves in some cases less subresultant polynomials.